Indonesia : Ninth Review Under the Extended Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The Indonesian authorities are to be commended for their continued strong policy performance under their arrangement with the IMF. The economy is sustaining steady growth despite a number of external and domestic shocks; inflation has continued to decline; and there has been an additional buildup of international reserves. Indonesia's fiscal policy remains geared toward achieving a significant fiscal consolidation and reduction in public debt. Progress has also been made in structural areas. The authorities are also encouraged to keep up the momentum of the privatization program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet